´´Inteligencia Emocional y Autoestima en los estudiantes de la Unidad Educativa ´´José María Román´´ Riobamba 2015-2016´´ - Alarcón Flores, Adriana Jacqueline (2017)
In the midst of a society in which the education of the emotions and feelings in the children has been a priority in the educational institutions as a strategy for the integral formation and total of the personality of the students, and thus to favor not only their psychological –emotional welfare, but also to influence positively on their self-steem and self-awareness. The present research work is a study on Emotional Intelligence and Self-Esteem in the students of Basis General Education, whose main objective is to determine how Emotional Intelligence influences on the self-esteem of this population. The methodology used in this research is quantitative in nature, the study results were obtained through two tests: Final Test of Emotional Intelligence for school children, composed of five items each consisting of twelve questions of different aspects: self-awareness, social skills , Empathy, self-control and emotional exploitation; In addition, the A-EP Test Questionnaire for the Asseeement of the Self-Esteem in Primary Education was used, consisting of twelve questions regarding self-concept. The population is made up of 113 students of the Fifth Year of Basic General Education of the Educational Unit '' José María Román''. The most significant findings obtained from this study are that in their great majority students are in an average level of emotional intelligence and a very similar percentage are in an mid-level of self-esteem, thus establishing a close relationship between both.